2023
DOI: 10.1200/op.22.00410
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives on Managing Chronic Pain After Curative-Intent Cancer Treatment

Abstract: PURPOSE: Among cancer survivors who have completed curative-intent treatment, the high prevalence and adverse consequences of chronic pain are well documented. Yet, research on clinicians' experiences with and perspectives on managing chronic pain among cancer survivors is critically lacking. METHODS: We conducted semistructured interviews with 17 clinicians (six oncology, three palliative care, and eight primary care) affiliated with an academic medical center. Interview questions addressed clinicians' experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…[10,18,30] Nonetheless, providers may underestimate the prevalence and severity of chronic pain among cancer survivors. [15] Similar to another study, [8] participants in our study reported sometimes feeling dismissed by providers when presenting with pain. They described inadequate pain assessment and some participants described minimizing their own pain for fear of being dismissed or seen as complaining to providers who may have saved their lives.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[10,18,30] Nonetheless, providers may underestimate the prevalence and severity of chronic pain among cancer survivors. [15] Similar to another study, [8] participants in our study reported sometimes feeling dismissed by providers when presenting with pain. They described inadequate pain assessment and some participants described minimizing their own pain for fear of being dismissed or seen as complaining to providers who may have saved their lives.…”
Section: Discussionsupporting
confidence: 89%
“…These include concerns about opioid addiction (particularly in the context of the ongoing overdose crisis), [9][10][11] limited access to multimodal pain treatment, 12 and limited provider training in managing chronic pain. [13][14][15] Patients may also under-report chronic pain to their providers during clinical encounters. 10 These challenges may be exacerbated in the cancer survivorship context, where care is often fragmented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain intensity and pain interference: BPI-SF scores categorized as 1-4 for mild, 5-6 for moderate and 7-10 for severe. [21] Depression: DASS-21 score categorized according to cut points used in Australian pain clinics, viz., normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27) or extremely severe (≥28).…”
Section: Categorical Variablesmentioning
confidence: 99%
“…11,12 Although chronic pain is widely recognized as a biopsychosocial phenomenon, 13 prior qualitative work inclusive of palliative care clinicians documents insufficient knowledge of managing psychosocial stressors in cancer survivors with chronic pain. 14 In addition, given the challenges to accessing multimodal comprehensive pain treatments, opioids often remain the mainstay of treatment, with cancer survivors prescribed long-term opioid therapy at 5 times the rate of the general population. 15 There is a need to develop a deeper understanding of the complex experience of cancer survivors living with chronic pain who do fall clearly into noncancer pain and acute cancer-related pain treatment paradigms.…”
Section: Introductionmentioning
confidence: 99%